A First Approach to the Execution of Construction Supervision Contracts in Public Projects in Peru - Morón Urbina, Juan Carlos (2023)
The purpose of this paper is to address a first approach to the execution of construction supervision contracts in public projects in Peru mains issues and challenges faced in the execution of construction supervision contracts, signed under Peruvian regulations for quality control and technical support in the contractual management of the construction of public works under the regime general and/or in the execution of concession contracts. Given the importance of these contracts in the development at the engineering or construction stage of an infrastructure investment project, their regulation, and the correct understanding of the nature of the provision of these specialized services is the central object of the present article. We briefly analyze the background of the figure of the “work supervisor” in Peruvian regulations, to identify its purpose and its scope in public works under the general regime and in concession contracts. Finally, in this article the main problems that are identified in the execution of this type of supervision contracts are raised and how they end up having a negative impact on the development of the construction of the work project, even conditioning its frustration.